Corporate social responsibility and SMEs: Evidence from a transition and a developed economy. Issue 5 (2nd August 2019) - Colovic, Ana; Henneron, Sandrine; Huettinger, Maik; Kazlauskaite, Ruta
Abstract : Purpose: This paper aims to investigate corporate social responsibility (CSR) in small and medium-sized enterprises (SMEs) in transition and developed economies. Design/methodology/approach: Building on social capital theory, the creating shared value approach and institutional theory, the authors study why and how six SMEs in the food sector implement CSR. Findings: The authors show that CSR adoption by SMEs is motivated by company values and beliefs, relationships with the local community, a desire to abide by rules and regulations and business motives. They also show that SMEs are involved in various CSR-related activities such as respecting their employees, infusing CSR in the supply chain and philanthropy. Originality/value: The findings suggest that although there are similarities between the CSR motives and activities of SMEs in developed and transition countries, there are also some differences, which can be explained by differences in institutions and related to the maturity of the CSR construct in each setting. The authors consequently call for a more holistic approach when investigating CSR across countries, in particular when such investigation concerns SMEs.